INCIDENCE AND PATTERN OF NATURAL DEATH DURING AUTOPSY AT PDU MEDICAL COLLEGE, RAJKOT REGION (Journal of Forensic Medicine & Toxicology, 2020)
Autopsy is an established tool to ascertain the cause of death in cases where clinician fails to reveals causes of death during on-going treatments or received dead bodies. The aim of our study was to define the etiology of natural deaths. The present study was carried out to find out the incidence and causes of natural deaths in cases brought for medicolegal autopsies. Age and sex wise incidence showed 820 males and 220 females with a male: female approximate ratio of 4:1. Highest number of cases (273) was observed in the age group of 51-60 years (26.25%). The commonest cause of death was found in cardio-vascular system among which coronary insufficiency was cause of death in 54.52% cases, followed by Other causes include respiratory system diseases, hepatic diseases, septicemia, central nervous system diseases and carcinoma etc.
Keywords: female; septicemia; carcinoma